Economic Role of Population Density - Yuri Yegorov (European Regional Science Association (ERSA), 2015)
The role of population density for economic activity was neglected in most part of economic theory. This paper is a review and extension of the previous works of the author in this field. So far, densities did not become common economic variables in economic analysis, and two countries with different densities of population and infrastructure but similar in macroeconomic parameters are treated as similar. One of the presented models is about an influence of population density on infrastructure development, and later on country potential for economic growth (Yegorov 2005a). Self-organization of production activity in space is elaboration of the ideas of von Thunen. When a city emerges as a center of industrial activity, it deforms the space, and agricultural land rent becomes a function of distance due to transport cost to bring the good to the market. Population density plays an important role in harvesting societies, i.e. those that depend on agriculture and natural resources. Too high population density decreases the natural endowment per capita, but eases the development of infrastructure, leading to existence of an optimal population density for economic growth (Yegorov, 2009). The trade-off between scale economies and transport costs leads to an optimal area served by a local monopolist. In the world with low population density competition might not even emerge because even monopolist can become bankrupt due to low demand density, especially in the environment of high transport costs. Such situation took place on the most part of Russian territory after liberalization that also lead to an increase in relative transport costs. Population density also can play role for an optimal size of a country. While there are many other reasons (mostly historical), spatial structure is also important. Land area of a country is considered as some capital bringing rent from natural resource extraction. The length of a border requires protection efforts and thus is a first type of cost. Commuting with the capital is another type of cost, and here the population density also matters. All these 3 factors enter with different power, and optimization with respect to linear scale give different results (Yegorov, 2005b). Literature 1. Yegorov Y. (2005a) Role of Density and Field in Spatial Economics. ? In: Yee Lawrence (Ed). ?Contemporary Issues in Urban and Regional Economics?. Nova Science Publishers, 2005, N.Y., p.55-78. 2. Yegorov Y. (2005b) Dynamically Sustainable Economic Equilibria as Self-Organized Atomic Structures (2005b) ? In: M.Salzano, A.Kirman, Eds., ?Economics: Complex Windows?, Springer-Verlag Italia, 2005, p.187-199 3. Yegorov Y. (2009) Socio-economic influences of population density. - Chinese Business Review, vol.8, No. 7, p.1-12.
Keywords: O18; Q10; R14; R40; 330; population density; optimization; economic growth; transport costs